Development and application of a 1K functional liquid chip for lactation performance in Bactrian camels - Guo, Lili; Dao, Lema; Liu, Bin; Wang, Jingyu; Liu, Zaixia; Ma, Fengying; Morigen, Bielige; Chang, Chencheng; Bai, Yinbatu; Guo, Yaqiang; Shi, Caixia; Cao, Junwei; et al. (Frontiers in Veterinary Science, 2024)
The advancement of genotyping platforms that are high-throughput, high-quality, highly flexible, and cost-effective is crucial for the progress of dairy breeding in Bactrian camels. In this study, we developed and evaluated a 1K functional liquid SNP array, specifically designed for milk performance of Bactrian camels. Utilizing RNA sequencing data from 125 lactating camels, we identified and selected 1,002 loci associated with milk production traits for inclusion in the SNP array. The array's performance was assessed using 24 randomly selected camels, demonstrating high overall SNP call rates (> 99%) and a remarkable 100% consistency in genotyping. Furthermore, the SNP array was employed to genotype 398 individuals, and was applied to population validation to assess the polymorphism of SNP sites. Our study results indicate that camels from six breeding areas from Northwest China share a similar genetic background regarding lactation functionality. This study highlights the array's potential to accelerate the breeding process of lactating Bactrian camels and provides a robust technical foundation for improving lactation performance.